Effect of whitening mouthrinses on color change of stained resin composites - Mailart, Mariane Cintra; Crastechini, Érica; Oliveira, Juliana Boa Sorte; Torres, Carlos Rocha Gomes; Caneppele, Taciana Marco Ferraz; Borges, Alessandra Buhler (Brazilian Dental Science, 2022)
Objective: The present study compared the effect of whitening mouthrinses (WM) on the color change of stainedresin composites (RC). Material and Methods: Cylindrical specimens (6mm-diameter and 1mm-thickness)were prepared with the following RC (n=60/group): Filtek Z350XT (Z350- methacrylate-based), Admira Fusion(AD- ormocer-based), TPH3 (TPH- methacrylate-based), and Beautifil II (BII- giomer/methacrylate-based).The initial color was assessed with reflectance spectrophotometer using CIE L*a*b* system. The specimenswere immersed in staining broth during 14 days, submitted to color evaluation (E1) and randomly allocatedin 4 subgroups (n=15), according to WM adopted: Listerine Whitening (LW-2% hydrogen peroxide), PlaxWhitening (PW-1.5% hydrogen peroxide), Bromelain/papain (BP-experimental solution), and Deionized water(DW-negative control). The whitening cycle consisted of RC immersion in WM for 1 min and in artificial salivafor 30 min, simulating 12 weeks, and final color assessment was performed (E2). Color change data wereanalysed by ANOVA and Tukey’s tests (a=5%). Results: After staining, TPH showed the lowest E1 valuesand Z350 showed the highest color change (p=0.001). The whitening effect promoted by LW was significantlyhigher than color alteration obtained with PW (E2), and BII showed the highest color change values (E2) afterwhitening cycle. Conclusion: LW exhibited the greatest whitening potential on stained RC, mainly with theGiomer (Beautifill II) and the Ormocer-based (Admira Fusion) materials. Bromelain/papain solution showedno whitening effect on stained RC.KEYWORDSGiomer; Hydrogen peroxide; Ormocer; Resin composite; Whitening mouthrinses.